2014
DOI: 10.1016/j.bone.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblastic cell secretome: A novel role for progranulin during risedronate treatment

Abstract: It is well established that osteoblasts, the key cells involved in bone formation during development and in adult life, secrete a number of glycoproteins harbouring autocrine and paracrine functions. Thus, investigating the osteoblastic secretome could yield important information for the pathophysiology of bone. In the present study, we characterized for the first time the secretome of human Hobit osteoblastic cells. We discovered that the secretome comprised 89 proteins species including the powerful growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…Documented results showed that recombinant human PGRN can induce phosphorylation of mitogenactivated protein kinase in both HOBIT and osteocytic cells and induce cell proliferation and survival. Moreover, they found that Risedronate, a widely used bisphosphonate drug in the treatment of osteoporosis, can induce the expression and secretion of PGRN in the HOBIT secretome (16). These findings have shown the probable preventive effects of PGRN on osteoporosis by modulating bone loss.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Documented results showed that recombinant human PGRN can induce phosphorylation of mitogenactivated protein kinase in both HOBIT and osteocytic cells and induce cell proliferation and survival. Moreover, they found that Risedronate, a widely used bisphosphonate drug in the treatment of osteoporosis, can induce the expression and secretion of PGRN in the HOBIT secretome (16). These findings have shown the probable preventive effects of PGRN on osteoporosis by modulating bone loss.…”
Section: Discussionmentioning
confidence: 73%
“…Similarly to this study, Romanello and cols. demonstrated the proliferative and pro-survival effects of PRGN on osteocyte-like cells (16). Likewise, a recent study by Oh and cols.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For our purposes, BCM can be prepared from fresh pig mandibles 10,11 . Proteomic analyses of BCM revealed the complex composition, including growth factors and constituents of the extracellular matrix 10 , also extending existing knowledge on the proteasome of whole bone 18,19 . Thus, BCM should reflect the released activity of various modifications of bone grafts in vitro.…”
Section: Introductionmentioning
confidence: 70%
“…Hence, the importance of PGRN in inflammation remains quite controversial and may need to be clarified in other inflammatory diseases involving osteoporosis. More recently, it has been shown that OBs produce a great deal of PGRN, which affects chondrogenesis (17). Therefore, we are interested in the roles of PGRN in bone biology.…”
mentioning
confidence: 99%